2010
DOI: 10.1021/jp102334t
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations of Rotational Energy Transfer in HBr + He Collisions

Abstract: Rotational relaxation rates for HBr(v = 1) colliding with helium atoms at room temperature have been measured using a time-resolved optical-optical double resonance technique. Rotational state selective excitation of v = 1 for rotational levels in the range J = 1-9 was achieved by stimulated Raman pumping. The population decay in the prepared states and the transfer of population to nearby rotational states was monitored via 2 + 1 resonance-enhanced multiphoton ionization (REMPI) spectroscopy using the g(3)Σ(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The background loss rate, k loss , varied between 2 × 10 4 and 7 × 10 4 s –1 , as determined independently from the unbleached transient data recorded in each scan. The functional form of single exponential decay to a final offset is exact for a two-state reversible system returning to equilibrium, as if the bath of all unobserved states were an undifferentiated kinetic species with a single reverse rate to the probed level, and often provides a good, though not exact representation of total RET kinetics. , By restricting the temporal region of interest to the initial stages of relaxation, prior to attainment of full equilibrium, the functional form is flexible enough to represent accurately the type of decelerating decay illustrated in Figure c for times as long as 2 or 3 time constants. The adjustable parameter A ∞ can then be reinterpreted not as the true equilibrium Boltzmann population ratio of the detected state to the sum of all other states, but rather as an empirical deceleration parameter, representing the curvature of the initial log decay.…”
Section: Resultsmentioning
confidence: 99%
“…The background loss rate, k loss , varied between 2 × 10 4 and 7 × 10 4 s –1 , as determined independently from the unbleached transient data recorded in each scan. The functional form of single exponential decay to a final offset is exact for a two-state reversible system returning to equilibrium, as if the bath of all unobserved states were an undifferentiated kinetic species with a single reverse rate to the probed level, and often provides a good, though not exact representation of total RET kinetics. , By restricting the temporal region of interest to the initial stages of relaxation, prior to attainment of full equilibrium, the functional form is flexible enough to represent accurately the type of decelerating decay illustrated in Figure c for times as long as 2 or 3 time constants. The adjustable parameter A ∞ can then be reinterpreted not as the true equilibrium Boltzmann population ratio of the detected state to the sum of all other states, but rather as an empirical deceleration parameter, representing the curvature of the initial log decay.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the theoretical research of modified energy gap(MEG)and statistical power exponential gap (SPEG) [12], the experimental results demonstrated that the theoretical value of the RET rate constant agreed well with the experimental values. The time-resolved two-photon resonance enhancement technique was used to study the rotational relaxation rates of HBr (v = 1, J = 0-9) and He atoms [13]. The total depopulation rate constant was in the range of…”
Section: Introductionmentioning
confidence: 99%
“…Heaven et al [18,19] studied the rotational energy transfer between the HBr (v = 1, J) vibrational state and the ground states of HBr and He atoms. The experimental results demonstrate that the theoretical value of the rotational relaxation rate is in good agreement with the experimental value.…”
Section: Introductionmentioning
confidence: 99%